EFEKTIVITAS RESTRUKTURISASI PEMBIAYAAN, FDR DAN NPF TERHADAP PROFITABILITAS PERUSAHAN SELAMA MASA PANDEMI COVID-19 (STUDI PADA BANK SYARIAH DI INDONESIA) - Meilinda, Bunga Putri; Muttaqin, Aminullah Achmad (I-Economics, 2021)
This study aims to determine the effect of the financing restructuration, financing to deposit ratio, and non performing financing on company’s profitability represented by return on assets during the covid-19 pandemic.the analytical method used is quantitative research with panel data regression alaysis techniques. The result of this study indicate that financing restructuration has a positive significant effect on the company’s profitability during the covid-19 pandemic of 0,430932 and financing to deposit ratio has a negative effect on the company’s profitability during the covid-19 pandemis of -0,428821. Meanwhile, non performing financing doesn’t have a significant effect on the company’s profitability during the covid-19 pandemic.